2013
DOI: 10.1016/j.ejon.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Living into old age with the consequences of breast cancer

Abstract: Purpose of the research: Breast cancer survival rates are improving with over 60% likely to live 20 years. As 30% diagnoses occur in women over 70 the prevalence of breast cancer survivors living into older age is increasing. The specific needs and experiences of this group have rarely been addressed. This study aimed to explore older women's experience of living with breast cancer alongside other health conditions, and to identify their information and support needs and preferences. Methods and sample: Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 17 publications
2
49
0
1
Order By: Relevance
“…Consistently, the findings from this study show that older women with breast cancer in Malaysia do seek information on breast cancer (Wong et al, 2011). The most preferred sources of information are medical professionals (Tomaka, 2006) and individuals such as family and friends (Carlsson, 2009;Fenlon et al, 2012). The respondents prefer to seek information from family and friends because both parties can also fill their emotional needs (Carstensen, 1999).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Consistently, the findings from this study show that older women with breast cancer in Malaysia do seek information on breast cancer (Wong et al, 2011). The most preferred sources of information are medical professionals (Tomaka, 2006) and individuals such as family and friends (Carlsson, 2009;Fenlon et al, 2012). The respondents prefer to seek information from family and friends because both parties can also fill their emotional needs (Carstensen, 1999).…”
Section: Discussionsupporting
confidence: 60%
“…Recent research shows that older women with breast cancer expressed a preference for information direct from health professionals (Fenlon et al, 2012) and not prefer to use newspapers and narratives (Gaglio et al, 2012). Furthermore, a study of 302 breast cancer patients found that women age 75 years and older were most likely to obtain information from their breast cancer physicians, friends, family (Carlsson, 2000) or member of their healthcare team (Tomaka, 2006).…”
Section: Older Women Breast Cancer Survivors: Decision Making Sourcementioning
confidence: 99%
“…The long-term impacts of breast cancer and therapy on everyday life need further investigation [351]. There are implications for cardiac functioning, osteoporosis, neuropathy, cognitive dysfunction, lymphoedema and shoulder mobility on the ability to maintain independence [352]. …”
Section: Resultsmentioning
confidence: 99%
“…O mesmo demonstrou que as mulheres mais jovens apresentaram maior dificuldade com relação à sua própria imagem corporal 7 . Já em outro estudo, mulheres mais velhas apresentaram maior dificuldade em olhar para o seu corpo, mesmo após anos de cirurgia, demonstrando-se ansiosas para preservar a sua imagem corporal ideal 12 .…”
Section: Discussionunclassified